The Impact of Fatigue on Jump Shot Height and Accuracy Over a Longer Shooting Distance in Basketball (Baltic Journal of Sport and Health Sciences, 2018)
This study basically aimed to establish how a gradual increase in effort (fatigue) affects the jump height and accuracy of shots at the basket. For this purpose, an elite basketball player, Primož Brezec, performed seven series of 20 shots from a distance of 7.24 metres. All shots were executed in four-second intervals and the height of each jump shot was measured. The accuracy of shots was established on the basis of the number of goals and distance from the centre of the ball to the centre of the rim of the basket. Thus, for each shot a kinematic analysis was applied using the APAS system to calculate the parabolas of ball ﬂ ight and the distance between the two points mentioned. During an individual series of shots the subject player performed a special basketball motor task consisting of running, a defensive slide and jumps. The effort gradually increased with each motor task and, in the meantime, the subject’s heart rate and concentration of lactates in his blood were measured. The results of the study show that the jump height decreases on average with each series of shots (with the exception of series two) and that the differences between the series are statistically signiﬁ cant (p < 0.01). There were no statistically signiﬁ cant differences between the individual series of shots in terms of shooting accu-racy and / or number of goals. The number of goals decreased drastically in the last series, i. e. in the conditions of maximum fatigue (heart rate: 197 beats / min, lactate concentration: 9.7 mmol / l). The average distance between the centre of the ball and the centre of the rim in the plane of the rim ranges between 13.5 and 16.6 cm, however, it does not increase with fatigue.Keywords: jump shot, kinematic analysis, accuracy, jump height, fatigue.